2023
DOI: 10.1007/s00167-023-07407-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased complications rates and inferior patient reported outcomes following total knee arthroplasty due to post‐traumatic osteoarthritis with previous fracture treatment: a systematic review

Abstract: Purpose This study aims to present the existing literature relating to patient-reported outcome measures (PROMs) and complications in patients undergoing total knee arthroplasty (TKA) due to posttraumatic osteoarthritis (PTOA) with prior fracture treatment around the knee compared with patients who underwent TKA because of primary osteoarthritis (OA). Methods A systematic review was undertaken and synthesised in accordance with the PRISMA guidelines by sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In a recent systematic review, Syrikas et al [11] demonstrated a higher postoperative complication rate with infections being the most common, a higher revision rate and inferior patient-reported outcomes in patients with TKA following PTO when compared to those of OA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent systematic review, Syrikas et al [11] demonstrated a higher postoperative complication rate with infections being the most common, a higher revision rate and inferior patient-reported outcomes in patients with TKA following PTO when compared to those of OA.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, PTO progresses and nonoperative treatment may fail. For end-stage PTO of the knee, total knee arthroplasty (TKA) is a common procedure that has been shown to alleviate pain and restore function [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations